Establishing a Halal Ecosystem to Eradicate Moral Degradation in Indonesian Education - Muhammad Umar Bahusin; Sakinah Izzati Nurrizqi; Ashifuddin Fikri; Salwa Hilda Febriza; Muhammad Dony Caprinosya; Muhammad Zakiy (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Moral degradation refers to a decline in a person's adherence to the social norms and ethical standards of society. This decline can be influenced by various factors, such as a child's environment and exposure to social media, which can lead to changes in behavior. As a result, this can disrupt the social order and contribute to feelings of social insecurity. In response to this issue, a research study was conducted to develop a